SIMULASI VIRTUAL REALITY PADA RUMAH SAKIT GRAHA AMERTA SURABAYA - Ahmad Hoirul Basori (Universitas Ahmad Dahlan, 2007)
In this research, we would like to present virtual reality application that will visualize Graha Amerta Surabaya hospital into Virtual environment. This 3D simulation is for helping people on remembering hospital area. There 3 different categories: road way around hospital, lobby reception and VIP room for patient. Guidance process involve Dijkstra algorithm for looking shortest path to specific location. The result of simulation still not perfect because of the coordinate of building still not precise. In other ways, there also difficulty of customize the building became look similar with the real, it’s because of the addition on building will increase the number of polygon, there fore memory needs will also increase.